Changes of metabolic profile and lts associotion with fat cow syndrome in high vielding cows during dry period and after parturation - Veysi Aslan; Ülker Eren; Mutlu Sevinç; İsmail Öztok; Kürşat Işık (Eurasian Journal of Veterinary Sciences)
This investigation was carried out on 17 head of Swiss Brown dairy cattle in Central Research Institute of Konya during winter until enel of spring. Blo ad sarnp/es were taken from jugu!ar ve in during 7 th. 8 th month of gestation and aftei birth and 15th. day after parturation. And blood gas analyses and other same chemical paramaters were maasureel by Blood Gas Analayzer and Autoonalyzer Instruments. At the same time, liver byopsi samples were obtained, from each cows during experiment. to observed any fat infiltration to liver. Blood ICa anel normCa concentrations were deeresed significantly at the parturation. Same paramaters were elevated significantly at 15 th day after parturation. Other metabolic profiles which maasureed were changed unsignificantly during the experiment. Fatt infiltration to liver was observed in a few cow but the level of fat inffitratian was not severe.